Clinical outcomes of intramedullary femoral nailing system to treat femoral fracture - Rawat, Pooja; Kumar, Mohit; Luthra, Gaurav (International Journal of Research in Orthopaedics, 2020)
Background: Femoral fractures are bone fracture involve femur, common injuries in adults. Intramedullary femoral nailing system is the recommended solution or treatment for fractures due to its high union rates. Methods: In this clinical inspection 30 patients were selected with bone fracture of femur, and treated by using intramedullary femoral nailing system (universal intramedullary cannulated femoral nail, expert femoral nail, gamma nail and retrograde femoral nail) manufactured by Auxein Medical Private Limited, Sonepat, Haryana, India. There are two types of patients used in this study, one is male (n=18) and another female (n=12). Patients physical fitness was also observed through American Society of Anesthesiologist. Results: Outcomes record from the patients using visual analog scale. Follow up of the patients were taken on 1st month, 6th month, and 12 months. Post-operative outcomes were good with none of the patients showing non-union of fracture site. There were no complications noticed related to intramedullary femoral nailing system in this study and hardware related complications were not encountered in this study also. Conclusions: Intramedullary nailing system provide excellent outcomes with high union and low complication rates in the management of bone fracture involve femoral in patients.